THU0060 Alterations of splicing in leukocytes from rheumatoid arthritis patients and its influence on the autoimmune, inflammatory and atherothrombotic profile of the disease. potential role of u4atac. (12th June 2018) - Ibáñez-Costa, A.; Perez-Sanchez, C.; Pedraza-Arévalo, S.; del Río-Moreno, M.; Ruiz-Limón, P.; Barbarroja, N.; Jiménez-Gómez, Y.; Ábalos, M.C.; Segui, P.; Collantes, E.; Castaño, J.P.; Luque, R.M.; et al.
Abstract : Objectives: The aim of this study was the identification, in leukocytes of Rheumatoid Arthritis (RA) patients, of the alterations present in the spliceosome and the machinery responsible for the splicing, as well as their influence on the activity of the disease and its atherothrombotic profile. Methods: We evaluated, using a microfluidic qPCR array (Fluidigm), a set of 45 elements of the splicing machinery: the complete major and minor spliceosome components and a series of splicing factors with potential pathological role. Monocytes, neutrophils and lymphocytes of purified from 74 RA patients and 29 healthy donors (HD) were assessed. In parallel, extensive clinical/serological evaluation, and correlation and association analyses were carried out. Results: A significant alteration in several components of the spliceosome was observed in all the three leukocyte subtypes from RA patients compared to HD. Various spliceosome components were specifically altered in different leukocyte subtypes; it should be noted that a general downregulation was observed. Likewise, it was striking that 7 elements, including two small nuclear RNA (snRNU) of the major spliceosome (U1 and U5), the snRNA of the minor spliceosome, U4atac, and the splicing factors RBM3, RBM17, SAM68 and SRSF10 showed the same alteration pattern: all significantly reduced in the 3 leukocyte subtypes of patients with RA, except for U4atac, which was consistently over expressed and virtually absent in HD leukocytes. Although this process needs further analysis, it is likely that the overexpression of U4atac could interfere in the normal functioning of the major spliceosoma, by binding to U5, thus altering the splicing of most introns (>99%), favouring non-canonical splicing, and generating aberrant proteins involved in the development of this pathology. Correlation and association studies showed a significant association between the expression levels of the 7 splicing factors cited and several clinical/serological parameters, including the activity of the disease, the positivity for anti-CCP and RF antibodies, and the expression of different inflammatory mediators. Likewise, reduced values of other splicing factors, differentially deregulated in the three leukocyte subtypes, were associated with radiological involvement, as well as with the presence of atheroma plaques, hyperlipidemia and arterial hypertension. Conclusions: We have identified specific alterations in the splicing machinery of leukocytes from RA patients, associated with the activity of the disease, as well as with its inflammatory and atherothrombotic profile. Altogether, the generalised reduction of multiple elements of the splicing machinery and the consistent elevation of U4atac will deem necessary to examine the possible role of this snRNA in the alteration of the spliceosome in the near future, as well as its specific implication in the regulation of the expression of key proteins in the pathology of RA. Acknowledgements: Junta de Andalucía (CTS-7940) and ISCIII (PI15/01333 and RIER RD16/0012/0015) co-funded with FEDER funds Disclosure of Interest: None declared